Laser-induced graphene incorporated with silver nanoparticles applied for heavy metal multi-detection - Jeong, Seongeun; Yang, Sung wook; 이이재; Lee, Soo Hyun (Royal Society of Chemistry, 2023)
In this paper, the fabrication of silver nanoparticle/laser-induced graphene (AgNP/LIG) electrodes for the multi-detection of cadmium (Cd), lead (Pb), and copper (Cu) ions using a square wave anodic stripping voltammetry (SWASV) technique is described. Compared to conventional fabrication methods of graphene, a LIG was fabricated by a fast and simple method on a polyimide film by exposure to an infrared CO2 laser. To enhance the performance of the sensors, AgNPs were incorporated with a LIG for heavy metal ion multi-detection. The proposed AgNP/LIG heavy metal sensor showed superior performance to that fabricated by an in situ bismuth method, even for simple fabrication and experimental procedures. The sensor has high sensitivity (e.g., 0.24, 0.06, and 0.42 μA μg？1 L for Cd, Pb, and Cu ions, respectively), low limit of detection (0.1 μg L？1 for Cd, Pb, and Cu ions) and wide linear ranges (0.0 to 120.0 μg L？1 for Cd, Pb, and Cu ions). Finally, the measurement of concentrations of heavy metal ions in tap water and drinking water was performed for Cd, Pb, and Cu ions. The measurement results confirmed sensitivities of 0.07, 0.07, and 0.06 μA μg？1 L for drinking water and 0.03, 0.04, and 0.02 μA μg？1 L for tap water, and high linearity of R2 ？ 0.99.